Advances in transparent glass–ceramic phosphors for white light-emitting diodes—A review. Issue 3 (March 2015) - Chen, Daqin; Xiang, Weidong; Liang, Xiaojuan; Zhong, Jiasong; Yu, Hua; Ding, Mingye; Lu, Hongwei; Ji, Zhenguo
Abstract Currently, the major commercial white light-emitting diode is the phosphor converted LED made of blue-emitting chip and Y3Al5O12:Ce3+ yellow phosphor dispersed in organic silicone. However, the organic binder in high-power device ages easily and turns yellow due to accumulated heat emitted from chip, which adversely affects the device properties such as luminous efficacy and color coordination, and therefore reduces its long-term reliability as well as lifetime. In this mini-review article, we provide an overview of recent progresses in developing transparent inorganic glass–ceramics phosphors excitable by blue chip, as an alternative to conventional polymer-based phosphor converter, for construction of high-power white light-emitting diodes. Two kinds of synthesis routes, glass crystallization and low-temperature co-sintering, are discussed in detail. Afterwards, the materials design, structure/property optimization as well as glass–ceramic-based WLED devices construction are summarized. Finally, challenges and future advances for the realization of transparent glass–ceramics in commercial applications will be presented.